ONLINE SHOP COMMUNICATION STRATEGY CEMEAL_AN IN MARKETING ITS PRODUCTS ON SOCIAL MEDIA - Namira Fitria; Parlin Harbet (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Marketing communication strategies have an important role in the success of selling a product. Then marketing communication can also arouse and develop consumer awareness of the product/service of a business so that consumers are aware of the products/services offered. The purpose of this study is to find out how the marketing communication strategy carried out by online shops Cemeal_an in marketing their products on Instagram. Descriptive qualitative research is research using the case study method (case study). The results of this study show that the marketing communication strategies carried out by Cemeal_an through Instagram social media are proven not all to meet the existing marketing mix, but their consumers know the information about the product quite clearly. The selection of media used should be more optimized and support marketing communication activities in other ways so that the application of marketing communication can run more to keep up with the development of a very modern era like today.